PENGARUH BERAT DAN UKURAN BET TERHADAP AKURASI DAN STABILITAS PUKULAN DALAM PERMAINAN TENIS MEJA - Mirnawati Bakari; Ardin Abdul Gani; Giofandi Samin (Universitas Muhammadiyah Cirebon, 2026)
This study aimed to analyze the effect of paddle weight and size on stroke accuracy and stroke stability in table tennis. The research employed a quantitative approach using an experimental method involving 20 students from the Sports Science Study Program at Muhammadiyah University of Gorontalo. All participants were tested using two types of paddles with different characteristics: Paddle A weighing 150 grams and measuring 15 × 14 cm, and Paddle B weighing 175 grams and measuring 16 × 15 cm. The research instruments consisted of an accuracy test and a stroke stability test. Data were analyzed using a paired-sample t-test at a significance level of 0.05. The results showed that the use of Paddle A produced an average stroke accuracy score of 74.14%, while Paddle B yielded an average score of 68.41%. Statistical analysis revealed a significance value of 0.005, indicating a significant effect of paddle weight and size on stroke accuracy. In addition, the stroke stability score achieved using Paddle A was 8.20, which was higher than the score obtained using Paddle B (6.45). Based on these findings, it can be concluded that paddle weight and size significantly influence stroke accuracy and stability in table tennis. Selecting appropriate paddle characteristics can help improve players’ technical performance, particularly among novice players.